DFNA8/12 Caused by TECTA Mutations is the Most Identified Subtype of Non-syndromic Autosomal Dominant Hearing Loss - Hildebrand, Michael S.; Morín, Matías; Meyer, Nicole C.; Mayo, Fernando; Modamio Høybjør, Silvia; Mencía, Ángeles; Olavarrieta, Leticia; Morales Angulo, Carmelo; Nishimura, Carla J.; Workman, Heather; DeLuca, Adam P.; del Castillo, Ignacio; et al. (My University, 2011)
The prevalence of DFNA8/DFNA12 (DFNA8/12), a type of autosomal dominant non-syndromic hearing loss (ADNSHL), is unknown as comprehensive population-based genetic screening has not been conducted. We therefore completed unbiased screening for TECTA mutations in a Spanish cohort of 372 probands from ADNSHL families. Three additional families (Spanish, Belgian and English) known to be linked to DFNA8/12 were also included in the screening. In an additional cohort of 835 American ADNSHL families, we preselected 73 probands for TECTA screening based on audiometric data. In aggregate, we identified 23 TECTA mutations in this process. Remarkably 20 of these mutations are novel, more than doubling the number of reported TECTA ADNSHL mutations from 13 to 33. Mutations lie in all domains of the ¿-tectorin protein,including those for the first time identified in the entactin domain, the vWFD1, vWFD2 and vWFD3 repeats, and the D1-D2 and TIL2 connectors. While the majority are private mutations, four of them ¿ p.Cys1036Tyr, p.Cys1837Gly, p.Thr1866Met and p.Arg1890Cys ¿ were observed in more than one unrelated family. For two of these mutations founder effects were also confirmed. Our data validate previously observed genotype-phenotype correlations in DFNA8/12 and introduce new correlations. Specifically, mutations in the N-terminal region of ¿-tectorin (entactin domain, vWFD1 and vWFD2) lead to mid frequency NSHL, a phenotype previously associated only with mutations in the ZP domain. Collectively, our results indicate that DFNA8/12 hearing loss is a frequent type of ADNSHL. Keywords DFNA8; DFNA12; TECTA; mid-frequency hearing loss; high-frequency hearing loss